Akuntabilitas Pengelolaan Keuangan Desa di Kabupaten Jombang - Lina Nasihatun Nafidah; Nur Anisa (Akuntabilitas, 2017)
This study aims to determine the accountability of village financial management that includes planning implementation administration reporting accountability of financial management of village finances in Jombang regency. The research method used qualitative descriptive by compiling the financial management of Sumbermulyo village in conformity with the Local Head of Government Regulation Number 33 of 2015 on Management of Village Finance.  With data collection techniques through interviews and direct observation of the object of research.  Determination of observation area is done by considering the small amount of village fund acceptance or allocation of village fund. The results of this study indicate that based on Regent Regulation No. 33 of 2015 on the management of Village Finance outline management of Village Finance has reached accountability.  In addition village counseling is still needed from the local government to intensively assist the village to realize accountability of village financial management.